Amelioration in manganese uptake by a low-cadmium rice cultivar with application of several manganese fertilizers. Issue 5 (3rd September 2021) - Suda, Aomi; Abe, Tadashi; Ishikawa, Satoru
ABSTRACT: We evaluated the use of manganese-containing amendments (Mn amendments) to improve the Mn uptake of a low-cadmium (Cd) rice cultivar, Koshihikari Kan No.1 (Oryza sativa L.), with a loss of function in the OsNramp5 that transports Mn and Cd, which was developed from an elite japonica cultivar Koshihikari. A flooded soil incubation experiment demonstrated that an increase of dissolved Mn in soils was induced by adding all 14 Mn amendments and was highly dependent on the citric acid-extractable Mn in the amendment. From the result of the incubation experiment, we selected three Mn amendments, namely, SM-1 (remarkably high Mn availability), FME-2 (high Mn availability), and SM-3 (moderate Mn availability) for a pot experiment. The pot experiment was carried out using two kinds of Mn-deficient soils with different pH (soil A and B). Manganese uptake by Koshihikari Kan No.1 was only less than one-tenth of that by Koshihikari grown on the same kinds of control soils. Dissolved Mn in soils and Mn uptake by Koshihikari Kan No.1 were substantially improved with the application of Mn amendments in the order SM-1 > FME-2 > SM-3; however, the magnitude was much more prominent in soil A than soil B. Lower soil solution pH of soil A would promote Mn dissolution from amendments and prevent dissolved Mn from adsorption on solid phase. Manganese uptake by Koshihikari Kan No.1 increased linearly with the increased dissolved Mn in the observed range ( R 2 = 0.972, p < 0.001 for soil A and R 2 = 0.978, p < 0.001 for soil B). We concluded that the application of Mn amendment to Mn-deficient soils would be a promising countermeasure to ensure the healthy growth of Koshihikari Kan No.1. Additionally, soil pH control along with the application of Mn amendment would be of significance to improve the effectiveness of the application. The findings provide useful information for soil management to enhance Mn uptake by using the existing and future low-Cd cultivars with the mutant osnramp5 allele.